Testimony: María Rapela, a Costa Rican artist In Berlin - Herrera Rapela, María Luisa (2021)
A testimony that collects some experiences and reflections of the Costa Rican visual artist María Rapela in Germany and how she got involved in cultural management, coordinating the Fieber Festival a collaborative and self-managed platform of Ibero-American migrant women artists in Berlin between 2011 and 2017.